COVID-19 dengan Komorbid Tuberkulosis Paru dan Diabetes Melitus - Muthia Faurin; Fauzar Fauzar; Roza Kurniati; Alexander Kam; Eva Decroli (Fakultas Kedokteran, Universitas Andalas, 2021)
A 61-year-old man was admitted a confirmed COVID-19 with comorbid pulmonary tuberculosis and type 2 diabetes mellitus. The patient was given favipiravir therapy, category 1 of antituberculosis drug, and insulin therapy. The patient responded well to therapy with improved clinical and laboratory indicators. Key words: COVID-19, pulmonary tuberculosis, diabetes mellitus